VARIABILITY OF AGRONOMIC TRAITS IN VEGETABLE PEA (PISUM SATIVUM L.) GENOTYPES - Zec, Srđan (Journal of Agricultural Sciences (Belgrade), 2024)
In the course of this study, a total of 12 vegetable pea genotypes of different vegetation period were subjected to phenotypic characterization. The vegetable pea genotypes are a part of the collection maintained at the Institute of Field and Vegetable Crops Novi Sad. The plant material included 10 promising lines and two released cultivars, Tamiš and Dunav. The trial was carried out in 2022. It was set up at the Rimski Šančevi site, as a randomized block design in five replications. A total of 14 agronomic traits were analyzed. The obtained research results revealed divergence in the investigated plant material. The statistical significance of all sources of variation was determined by the LSD test. The height of the first fertile node stood out as the most variable feature, with a coefficient of variation of 40.54%. The tested genotypes were clustered into two groups and two subgroups within the second group. The correlation analysis of the examined quantitative traits revealed the existence of several statistically significant positive and negative correlations. Some of the most significant positive correlations were established between grain weight per plant and the number of grains per plant and the yield of technologically mature grain, while pod width and the number of fertile nodes per plant had the most negative correlations with the other tested traits.